Raising Healthy Children: Age Five - Claire Marie Fassett; Karla P Shelnutt (EDIS)
This publication is designed to give you some information about the social, mental, and physical development of your five-year-old child. This new 5-page fact sheet discusses nutrition, eating behaviors, healthy food options, cooking activities, and physical activity. Written by Claire Marie Fassett and Karla P. Shelnutt, and published by the UF/IFAS Department of Family, Youth and Community Sciences, January 2018. http://edis.ifas.ufl.edu/fy1475